Living Standards Analysis Model: The First Prototype - Anita King (New Zealand Government, The Treasury, 2018)
How do we understand the synergies and trade-offs of a given policy on area beyond that policy, such as the effect of housing on health and on income? How do we choose between policies in completely different areas, such as an education policy and a health policy? Treasury's Living Standards Framework provides one possible starting point, but it provides little assistance tracing the many dependencies between policy areas. A model that includes those dependencies could help. The Living Standards Analysis Model (LSAM) is designed to do this. A first prototype of the model has just been developed. This model includes all eleven aspects of wellbeing as described by the OECD's How's Life? framework and linkages between the different aspects for a small open economy. Most models for studying wellbeing only include one or two aspects, missing the rich set of interactions that can occur with greater coverage. As an early prototype, this version of the model does have many flaws and requires significant further development, but it forms a basis for creating an improved model as well as providing some qualitatively useful results. The model is loosely based on a stocks-and-flows type of model, with a small general equilibrium model covering the market economy part of the model. This paper is focussed on the description of the model.
Keywords: C65; D58; H50; I31; Q21; Q31; 330; wellbeing; wellbeing model; living standards; sustainability; stock and flow; CGE; health; education; environment; housing; civic engagement; jobs; income; wealth; life satisfaction; work-life balance; social connection; safety; Better Life Index